Does gaze direction influence cycling effort? - Sem Otten; Ruud J. R. Den Hartigh; Frank T. J. M. Zaal; Benoît G. Bardy; Christophe Gernigon (PLoS ONE, 2025)
Cycling effort can be influenced by the speed of the optic flow to which individuals are exposed. The present study tested whether gazing toward proximal (e.g., the road in front) versus distal areas (e.g., the horizon ahead) would influence cycling effort. We expected that gazing toward proximal areas would generate a feeling of “momentum” and thereby increase efforts. Twenty-eight cyclists completed two 20-minute trials on their bicycle in a VR environment, aiming to outperform the power output they exerted during a baseline trial. Their gaze direction was guided through a virtual frame, either aimed at the road immediately in front of the cyclist (proximal) or at the horizon (distal), in counterbalanced order. A repeated measures ANCOVA, with baseline power as a covariate, showed no significant difference in exerted effort between the proximal and distal conditions, and no significant interaction effect between condition and baseline power. This finding is not in accordance with previous research, in which occlusions of proximal and distal areas of the visual field did influence cycling efforts. Taken together, the results suggest the importance of peripheral vision in speed perception, which may influence cycling effort.